Girls’ Education: Danger and Resistance reflected in `I am Malala` by Malala Yousafzai and Christina Lamb and `My Name is Parvana` by Deborah Ellis - Ria Hendriani (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2017)
This study attempts to compare dangers and resistances faced by main characters in getting education, especially girls’ education. It also analyzes the significant issues of education in I am Malala and My Name is Parvana by using the concept of comparative literature in American school discipline. This study applies liberal feminism theory. The research findings can be formulated as follows: 1) there are three barriers endangering girls in getting education such as the weak position of women in society, poverty and conflict; 2) the resistances done by both characters to reach equal position in education. They strive to get better education and criticize the inequalities. The resistances in both literary works are conducted in difference ways. Malala argued that woman should be treated as equals as men; therefore, she never gives up in resisting dangers although she was shot by Taliban. Meanwhile, Parvana argued that there must be equality of role between women and men. Unfortunately, her effort fails and she gives up; 3) the significant issues, Malala and Parvana are aware of the advantages of education; therefore, they resist all dangers they faced. Finally, they become symbol of strong and independent women. In conclusion, both literary works raise clear issues about gender inequalities and the characters’ resistances in getting education.